2016
DOI: 10.1200/jco.2016.34.2_suppl.565
|View full text |Cite
|
Sign up to set email alerts
|

The role of metastasectomy in patients with renal cell carcinoma with sarcomatoid dedifferentiation: A matched controlled analysis.

Abstract: Purpose-Management of metastatic sRCC remains a therapeutic challenge with no standard treatment strategies. Our objective was to evaluate whether metastasectomy has any survival benefit in patients with metastatic sRCC treated with radical nephrectomy (RN).Patients and Methods-From an institutional database of 273 patients with sRCC treated with nephrectomy, we matched 80 patients with synchronous and asynchronous metastasis for age, ECOG performance status, histology and lymph node (LN) status. Matched pairs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…16 Among patients with mRCC who receive targeted therapy, concordance of risk prognostication between the MSKCC score and the IMDC model is approximately 0.66, likely indicative of the ongoing, continued need for additional refinements to prognostication methods. 90 Conversely, any sarcomatoid component was independently associated with poor OS among patients with brain metastases who received local therapy. Overall, among patients who undergo metastasectomy, several indicators consistently are described as independently associated with survival outcomes, irrespective of mRCC location or modality of locally directed therapy.…”
Section: Prognostic Models and Risk Stratificationmentioning
confidence: 99%
“…16 Among patients with mRCC who receive targeted therapy, concordance of risk prognostication between the MSKCC score and the IMDC model is approximately 0.66, likely indicative of the ongoing, continued need for additional refinements to prognostication methods. 90 Conversely, any sarcomatoid component was independently associated with poor OS among patients with brain metastases who received local therapy. Overall, among patients who undergo metastasectomy, several indicators consistently are described as independently associated with survival outcomes, irrespective of mRCC location or modality of locally directed therapy.…”
Section: Prognostic Models and Risk Stratificationmentioning
confidence: 99%
“…3,6,[15][16][17][18][19][20] The benefit of cytoreductive nephrectomy is not well defined in the era of targeted therapy; however, many studies showed improved OS in patients treated with cytoreductive surgery. [22][23][24] In the present study, nephrectomy was not universally performed because this decisions was left to the discretion of the surgeon. Third, this study included Asian patients, and therefore, it is possible that outcomes were affected by ethnic differences between study populations.…”
Section: Discussionmentioning
confidence: 99%
“…Renal carcinoma is one of the most common malignancies,it ranks ninth among the most common malignancies in men and 14th among women [1].Surgical approaches are the most common treatment for the early stage patients,but about 30% of patients have metastatic disease at presentation,and metastasis was found during surgery in 40 percent of patients [2].So Surgical treatments are not suitable for patients who have large unresectable or metastatic tumours,and those who do not want to undergo traditional surgery.Along with the development of treatment,the potential role of catheter-guided transarterial embolization(TAE) has been brought to renewed attention [3].For example, catheter-guided, renal artery embolization has become a safe and accepted treatment for renal trauma and renal angiomyolipoma [4].However,the role of TAE in the treatment of renal carcinoma is not well understood.Transarterial chemoembolization with drug-eluting beads kills tumor cells via the slow release of chemotherapy drugs after embolization of the tumor area.As a new embolization material,the safety and e cacy of drug-eluting beads in the treatment of hepatocellular carcinoma have been well demonstrated [5][6].In this study,we evaluate the feasibility,safety,and cytoreductive effect of transarterial chemoembolization on renal carcinoma,using drug-eluting beads saturated with pirarubicin. This study was approved by the Ethical Committee of A liated Hospital of Jining Medical University and followed the Declaration of Helsinki principles.…”
Section: Introductionmentioning
confidence: 99%